Distributed Space-Time Coding - Jing, Yindi; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Distributed Space-Time Coding (DSTC) is a cooperative relaying scheme that enables high reliability in wireless networks. This brief presents the basic concept of DSTC, its achievable performance, generalizations, code design, and differential use. Recent results on training design and channel estimation for DSTC and the performance of training-based DSTC are also discussed.
Introduction -- Distributed Space-Time Coding -- Distributed Space-Time Coding for Multiple-Antenna Multiple-Relay Network -- Differential Distributed Space-Time Coding -- Training and Training-Based Distributed Space-Time Coding.
Keywords: Engineering; Computer Communication Networks; Telecommunication; Engineering; Communications Engineering, Networks; Computer Communication Networks